The Robot Design Rancang Bangun Robot Pembersih Solar PV Dengan Sistem Pengendali Nirkabel - Nugroho, Oktavianus Ardhian; Apatya, Y.B. Adyapaka; Sanctos Perdana Tukan, Fransiskus Octario; Fredy Sakti, Yoannes (Infotekmesin, 2023)
One type of renewable energy source that is starting to be widely used at this time is the type of solar power generation. This system uses a photovoltaic effect where sunlight is converted into electricity. A solar cell usually consists of an arrangement of semiconductors cells often called solar PV modules. Obstacles arise when this PV module is dirty because the electrical power generated by the module becomes decreased. Manual cleaning is one of the ways to restore power to this PV. In this study, a cleaning robot machine has been designed and made that can clean solar PV modules automatically. The purpose of the study is to simplify the module maintenance process, ensure the safety and security of workers, reduce module damage, and ensure the cleanliness of the module. The design method has successfully made a robotic machine to clean solar PV modules. The test results also prove that the tool made can clean the module quickly and safely.